Transposição ou recontextualização? Sobre a produção de saberes na educação em museus de ciências - Martha Marandino (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
The transformation of scientific knowledge for teaching or public communication purposes, constitutes atime-space for the production of new knowledge. In this study, we analyse the processes of didactical/ museographical transposition and of recontextualization in spaces at science museums, in order to understand those mechanisms, which constitute the discourse expressed in expositions dealing with biological themes. Studies carried out in the educational and museological fields were used to understand the specificity, which museums impose on this process of production. In this paper, we give special attention to the construction of the theoretical framework used in the research process. The theoretical premises that were initially used were those of the concept of didactical/ museographic transposition. Based on a critique of the limits of this concept, new theoretical principles were utilised taking as their principal support the concept of recontextualization. Finally, we seek to discuss the possibilities and limits of the use of the concept of didactical/museographic transposition and analyse the challenges of working with the concept of recontextualization in order to understand those educational processes, which take place in spaces offered by science museums.